Electrostatic chuck
By adjusting the width and opening width of the electrostatic adsorption electrode on the ceramic substrate, the index Cs reaches 375 or above, the problem of local capacity changes caused by the reduction of porosity when the electrostatic capacity is improved, and the capacity stability and electrostatic adsorption effect are improved.
Patent Information
- Application Number
- JP2023152312
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
When the existing electrostatic chuck increases the electrostatic capacity to stably adsorb the silicone substrate, it is easy to cause excessive contact area between the ceramic substrate and the electrostatic adsorption electrode due to the decrease in porosity, causing peeling or residual stress caused by the difference in the thermal expansion coefficient, and thus causing local capacity changes.
By setting the width a and opening width b of the electrostatic adsorption electrode on the ceramic substrate, the index Cs=[1/ln{10(2D-a)/a}]/p reaches 375 or more, thereby ensuring a sufficient electrostatic capacity (50pF or more per 20mm diameter) and controlling the capacity change to within 10%.
It is achieved that without increasing the contact area of the electrostatic adsorption electrode, the electrostatic chuck has sufficient electrostatic capacity, and effectively suppresses capacity changes, while reducing peeling and residual stress caused by differences in thermal expansion coefficients.
Smart Images

Figure 2025044623000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrostatic chuck that attracts and holds a wafer. [Background technology]
[0002] Conventionally, there has been known an electrostatic chuck in which a mesh electrode (electrode for electrostatic attraction) made of woven linear conductive material is embedded in a ceramic sintered body (ceramic base material) such as AlN ceramics (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-212375 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to stably adsorb a substrate such as a silicon wafer to an electrostatic chuck, it is preferable to increase the electrostatic capacitance between the electrostatic adsorption electrode and the substrate in order to increase the Coulomb force. In the electrostatic chuck described in the above Patent Document 1, therefore, a mesh electrode woven with a twill weave or twill tatami weave, which has a lower opening ratio than a plain weave, is used as the electrostatic adsorption electrode in order to ensure the electrostatic capacitance. However, if the opening ratio is simply reduced in order to ensure the electrostatic capacitance, the contact area between the ceramic sintered body and the electrostatic adsorption electrode may become too large. In this case, there is a risk that peeling may occur at the interface between the ceramic sintered body and the electrostatic adsorption electrode due to a difference in CTE (linear expansion coefficient), or that the ceramic sintered body may be deformed due to residual stress. If peeling occurs at the interface between the ceramic sintered body and the electrostatic adsorption electrode, or if the ceramic sintered body is deformed due to residual stress, local variations in electrostatic capacitance may occur in the electrostatic chuck.
[0005] The present invention has been made in consideration of the above circumstances, and has an object to provide a technique for suppressing local variations in the capacitance of an electrostatic chuck while ensuring the capacitance necessary to stably attract a substrate to the electrostatic chuck. [Means for solving the problem]
[0006] According to an aspect of the present invention, a ceramic substrate having an upper surface and a lower surface facing the upper surface in a vertical direction, A metal electrode embedded in the ceramic substrate, In the electrode, electrode portions having a width a (m) and openings having a width b (m) are alternately arranged in a first direction perpendicular to the up-down direction, When the distance in the vertical direction from the upper surface of the ceramic base to the electrode is D (m) and the sum of the width a (m) and the width b (m) is p (m), the index Cs is expressed as: Cs=[1 / ln{10(2D-a) / a}] / p≧375 The electrostatic chuck is characterized in that Effect of the Invention
[0007] When the electrostatic adsorption electrode is formed of a mesh of woven metal wires, the width a (m) corresponds to the wire diameter, the sum p (m) corresponds to the wire pitch, which is the center distance between adjacent wires, and the vertical distance D (m) between the upper surface of the ceramic base material and the electrostatic adsorption electrode corresponds to the thickness of the ceramic insulating layer. When the electrostatic adsorption electrode is formed of a foil or plate material, the width a (m) corresponds to the width of the electrode portion, and the sum p (m) corresponds to the pitch, which is the center distance between adjacent electrode portions. By setting the index Cs=[1 / ln{10(2D-a) / a}] / p to 375 or more, it is possible to ensure a sufficient electrostatic capacitance (50 pF or more per 20 mm diameter) for an electrostatic chuck while suppressing the variation in electrostatic capacitance to within 10%. In other words, by selecting the thickness D of the ceramic insulating layer, the pitch p, and the width a of the electrode portion so that the above-mentioned index Cs is equal to or greater than the lower limit of 375, it is possible to ensure a sufficient capacitance (50 pF or more per 20 mm diameter) for use as an electrostatic chuck, while suppressing the variation in capacitance to within 10%, even in the case of an electrostatic attraction electrode having a certain porosity. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a perspective view of an electrostatic chuck 100 . [Diagram 2] FIG. 2 is a schematic diagram of the electrostatic chuck 100. [Diagram 3] FIG. 3 is a schematic explanatory diagram showing the shape of the electrostatic attraction electrode 124. As shown in FIG. [Figure 4] 13 is an explanatory diagram of an electrostatic attraction electrode 124 formed of a woven wire mesh. FIG. [Diagram 5] 1 is an explanatory diagram of an electrostatic attraction electrode 124 formed of a foil or plate material. [Figure 6] 1(a) to 1(e) are diagrams showing a flow of a method for producing the ceramic base 110. FIG. [Figure 7] 1(a) to 1(d) are diagrams showing the flow of another method for producing the ceramic base 110. FIG. [Figure 8] FIG. 8 is an explanatory diagram for explaining the measurement positions of the capacitance. [Figure 9] FIG. 9 is a table summarizing the results of Examples 1 to 17 and Comparative Examples 1 to 5. [Figure 10] FIG. 10 is an explanatory diagram of an electrostatic attraction electrode 124 in which an opening portion 124h having a hexagonal opening is formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Electrostatic Chuck 100> An electrostatic chuck 100 according to an embodiment of the present invention will be described with reference to FIGS. 1 and 2. The electrostatic chuck 100 according to this embodiment is used as a holding member for attracting and holding a semiconductor wafer such as a silicon wafer (hereinafter simply referred to as a wafer 10). In the following description, the up-down direction 5 is defined based on a state in which the electrostatic chuck 100 is installed so as to be usable (the state shown in FIG. 1). As shown in FIG. 1, the electrostatic chuck 100 according to this embodiment mainly includes a ceramic base material 110 and an electrostatic attraction electrode 124 (see FIGS. 2 and 3).
[0010] The ceramic base 110 is a member having a circular plate shape with a diameter of 12 inches (about 300 mm), and the wafer 10 to be held is placed on its upper surface 111. In FIG. 1, the wafer 10 and the ceramic base 110 are shown separated from each other to make the drawing easier to see. In this embodiment, the ceramic base 110 is formed of a sintered body of AlN ceramics containing aluminum nitride (AlN) as the main component. Here, containing AlN as the main component means that the content of AlN is 50% or more. The center line average roughness of the upper surface 111 of the ceramic base 110 is less than 1.0 μm. The ceramic base 110 is not limited to being formed of aluminum nitride, and can be formed of a sintered body of ceramics such as silicon carbide, alumina, and silicon nitride, for example.
[0011] Although not shown in the figure, the upper surface 111 of the ceramic substrate 110 can be arranged with a circular ring-shaped protrusion arranged on the outer periphery (outer edge) and a plurality of cylindrical protrusions arranged inside the circular ring-shaped protrusion.
[0012] A gas flow path (not shown) can be formed inside the ceramic base 110. The gas flow path can be used as a flow path for supplying gas to a space (gap) defined by the upper surface 111 of the ceramic base 110 and the lower surface of the wafer 10. Conversely, gas can be exhausted from the space (gap) defined by the upper surface 111 of the ceramic base 110 and the lower surface of the wafer 10 through the gas flow path. At this time, the pressure difference between the pressure outside the gap and the pressure inside the gap can be adjusted by adjusting the exhaust pressure. This allows the wafer 10 to be adsorbed toward the upper surface of the ceramic base 110.
[0013] 3, the electrostatic attraction electrode 124 has two semicircular electrodes 124a and 124b arranged to face each other with a predetermined distance between them, and has a generally circular shape as a whole. For example, the outer diameter of the electrostatic attraction electrode 124 can be set to 298 mm. The wafer 10 can be electrostatically attracted by applying a predetermined voltage (for example, ±500 V) to each of the electrodes 124a and 124b.
[0014] The electrostatic attraction electrode 124 can be formed of a mesh, foil, or plate material made of woven metal wires. The foil is a metal material having a thickness of less than 0.1 mm, and the plate material is a metal material having a thickness of 0.1 mm or more. As the metal material for forming the electrostatic attraction electrode 124, for example, a heat-resistant metal (high melting point metal) such as tungsten (W) or molybdenum (Mo) can be used. In this case, the purity of the tungsten or molybdenum is preferably 99% or more. Furthermore, as the metal material for forming the electrostatic attraction electrode 124, an alloy containing molybdenum and / or tungsten can also be used.
[0015] As shown in FIG. 4, when the electrostatic attraction electrode 124 is formed of a mesh of woven wires, the wire diameter (diameter) is a (m), the wire pitch is p (m), and the ceramic insulating layer thickness is D (m) (see FIG. 2). The wire pitch p is the center-to-center distance between adjacent wires, and the ceramic insulating layer thickness D is the vertical distance between the upper surface 111 of the ceramic base material 110 and the electrostatic attraction electrode 124. The wires with the wire diameter a (m) are arranged at a pitch p (m) in the vertical and horizontal directions that are perpendicular to each other, forming electrode portions 124e with a width a (m) arranged at a pitch p (m) in the vertical and horizontal directions, and opening portions 124h with a width b (m) (b = pa) arranged at a pitch p (m) in the vertical and horizontal directions. The weaving method of the wires is not limited to the weaving method (twill weave) shown in FIG. 4. For example, a plain weave can be similarly applied.
[0016] In this case, the index Cs is Cs=[1 / ln{10(2D-a) / a}] / p As described below, the exponent Cs can be 375 or greater.
[0017] Even when the electrostatic attraction electrode 124 is formed of a foil or plate material, a plurality of openings 124h arranged at a pitch p(m) can be formed in the foil or plate material. For example, as shown in Fig. 5, a plurality of openings 124h each having a square shape with a side length of b(m) in a top view can be arranged at a pitch p(m) in the vertical and horizontal directions that are perpendicular to each other. This forms electrode portions 124e with widths a(m) (a=pb) arranged at a pitch p(m) in the vertical and horizontal directions, and openings 124h with widths b(m) arranged at a pitch p(m) in the vertical and horizontal directions.
[0018] In this case, the index Cs is also Cs=[1 / ln{10(2D-a) / a}] / p As described below, the exponent Cs can be 375 or greater.
[0019] When the electrostatic attraction electrode 124 is formed of a W foil or plate, the multiple openings 124h can be formed by hole processing (machine processing such as punching or laser processing). Alternatively, for example, a mask of a predetermined shape can be formed on the upper surface of the metal foil using a photoresist or dry film, and the multiple openings 124h can be formed by etching using an etching solution containing a mixture of phosphoric acid, nitric acid, acetic acid, and water. Also, when the electrostatic attraction electrode 124 is formed of a mesh woven from metal wires, it is preferable to plain weave the wires, but it is also possible to form the electrode using other weaves such as twill weave.
[0020] Next, a method for manufacturing the electrostatic chuck 100 will be described. In the following, a case where the ceramic base 110 is made of aluminum nitride will be described as an example.
[0021] First, a method for manufacturing the ceramic base material 110 will be described. As shown in FIG. 6(a), granulated powder Q mainly composed of aluminum nitride (AlN) powder is put into a bed-equipped mold 601 made of carbon and pre-pressed with a punch 602. The granulated powder Q preferably contains 5 wt% or less of a sintering aid (for example, Y2O3). A metal (for example, Mo) foil or plate is prepared as the electrostatic adsorption electrode 124. Then, a plurality of openings 124h are formed in the electrostatic adsorption electrode 124 by etching or the like. Alternatively, the electrostatic adsorption electrode 124 can be formed by a mesh woven with metal (for example, Mo) wires. Next, as shown in FIG. 6(b), the electrostatic adsorption electrode 124 cut into a predetermined shape is placed on the pre-pressed granulated powder Q. The electrostatic adsorption electrode 124 is placed parallel to a surface perpendicular to the pressure direction (the bottom surface of the bed-equipped mold 601). At this time, a W pellet or a Mo pellet may be embedded at the position of the terminal 124T of the electrostatic attraction electrode 124 (see FIG. 3).
[0022] As shown in FIG. 6(c), granulated powder Q is further poured into the bed-equipped mold 601 so as to cover the electrostatic adsorption electrode 124, and pressed and molded with a punch 602. At this time, the amount of granulated powder Q covering the electrostatic adsorption electrode 124 can be adjusted so that the electrostatic adsorption electrode 124 is embedded at a depth of 0.3 mm or more. Next, as shown in FIG. 6(d), the granulated powder Q in which the electrostatic adsorption electrode 124 is embedded is fired in a pressed state. The pressure applied during firing is preferably 1 MPa or more. In addition, firing is preferably performed at a temperature of 1800° C. or more. Note that firing can also be performed multiple times. Next, as shown in FIG. 6(e), blind holes are machined up to the electrostatic adsorption electrode 124 in order to form the terminal 124T. Note that, if a pellet is embedded, blind holes are machined up to the pellet. Furthermore, a through hole for forming a gas flow path may be formed as necessary. In this case, a ceramic base material 110 having a gas flow path formed therein can be produced.
[0023] The ceramic substrate 110 can also be manufactured by the following method. As shown in Fig. 7(a), a binder is added to aluminum nitride granulated powder Q, which is then CIP molded and processed into a disk shape to produce an aluminum nitride compact 610. Next, as shown in Fig. 7(b), the compact 610 is degreased to remove the binder.
[0024] As shown in FIG. 7(c), a recess 611 for embedding the electrostatic adsorption electrode 124 is formed in the degreased molded body 610. The recess 611 may be formed in advance in the molded body 610. As described above, a metal foil or plate is prepared as the electrostatic adsorption electrode 124, and a plurality of openings 124h are formed in the electrostatic adsorption electrode 124 by etching or punching. Alternatively, the electrostatic adsorption electrode 124 is formed by a mesh woven from metal wires. The electrostatic adsorption electrode 124 is disposed in the recess 611 of the molded body 610, and another molded body 610 is laminated thereon. At this time, the thickness of the other molded body 610 can be adjusted so that the electrostatic adsorption electrode 124 is embedded to a desired depth. Next, as shown in FIG. 7(d), the laminated molded bodies 610 sandwiching the electrostatic adsorption electrode 124 are fired in a pressed state to produce a fired body. The pressure applied during firing is preferably 1 MPa or more. It is also preferable to perform the firing at a temperature of 1800° C. or higher. The firing can be performed multiple times. The steps after the production of the fired body are the same as those described above, and therefore the explanation is omitted.
[0025] The upper surface 111 of the ceramic base 110 thus formed is ground and polished. This makes it possible to adjust the distance in the vertical direction 5 from the upper surface 111 of the ceramic base 110 to the electrostatic attraction electrode 124. Furthermore, by performing sandblasting on the upper surface 111, it is also possible to form a plurality of convex portions and an annular convex portion on the upper surface 111. Note that, although sandblasting is a suitable processing method for forming the plurality of convex portions and the annular convex portion, other processing methods can also be used. EXAMPLES
[0026] The present invention will be further described below with reference to Examples 1 to 17. However, the present invention is not limited to the Examples described below. In addition, FIG. 9 shows a table showing the results of Examples 1 to 17 and Comparative Examples 1 to 5.
[0027] [Example 1] An electrostatic chuck 100 (see FIG. 2) of Example 1 will be described. In Example 1, a ceramic base material 110 having a diameter of 310 mm and a thickness of 25 mm was fabricated by the above-mentioned fabrication method using aluminum nitride (AlN) to which 5 wt % of a sintering aid (Y2O3) was added as a raw material. -4 (m) The electrostatic attraction electrode 124 was embedded at the lower position. In other words, the thickness D of the ceramic insulating layer (see FIG. 2) was 1.50×10 -4 The outer diameter of the electrostatic attraction electrode 124 was 298 mm. The electrostatic attraction electrode 124 was formed using a mesh made by plain weaving Mo wires. The wire diameter a of the wire was 5.00×10 -5 m, and the mesh size was 40 wires / inch. The wire pitch p, i.e., the center-to-center distance between adjacent wires, was 6.35 × 10 -4 In the electrostatic chuck 100 of Example 1, the value of the exponent Cs=[1 / ln{10(2D-a) / a}] / p was 402.6.
[0028] In the electrostatic chuck 100 of Example 1, a tungsten electrode having a diameter of 20 mm was placed on the upper surface 111 of the ceramic base 110, and the capacitance was measured with an LCR meter. As shown in FIG. 8, measurements were performed at the center (one location) of the ceramic base 110, on a concentric circle with a radius of 35 mm (four locations at equal intervals), on a concentric circle with a radius of 60 mm (eight locations at equal intervals), on a concentric circle with a radius of 85 mm (eight locations at equal intervals), on a concentric circle with a radius of 110 mm (16 locations at equal intervals), and on a concentric circle with a radius of 135 mm (16 locations at equal intervals). The average value of the measurements at these 53 locations was 55.0 pF. The difference between the maximum and minimum values of the measurements at these 53 locations was divided by the average value, and the value was evaluated as the variation in capacitance. In Example 1, the variation in capacitance was 3.8%.
[0029] [Example 2] The electrostatic chuck 100 of the second embodiment has an insulating layer thickness D of 3.00×10 -4 m, and the wire diameter a is 8.00 × 10 -5Except for the fact that the distance between the electrostatic chuck 100 and the surface of the electrostatic chuck 100 is 1 mm, the distance between the electrostatic chuck 100 and the surface of the electrostatic chuck 100 is the same as that of the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 1, the value of the index Cs was 377.3. When the electrostatic capacitance of the electrostatic chuck 100 of Example 2 was measured by the same method as that of Example 1, the average value of the measurements at 53 points was 51.5 pF, and the variation in the electrostatic capacitance was 8.5%.
[0030] [Example 3] The electrostatic chuck 100 of Example 3 has a mesh size of 50 wires / inch and a wire pitch p of 5.08×10 -4 m, the electrostatic chuck 100 of Example 3 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 3, the value of the index Cs was 503.2. When the electrostatic capacitance of the electrostatic chuck 100 of Example 3 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 65.3 pF, and the variation in the electrostatic capacitance was 6.4%.
[0031] [Example 4] The electrostatic chuck 100 of Example 4 has a mesh size of 50 pieces / inch and a ceramic insulating layer thickness D of 1.00×10 -3 m, and the wire diameter a is 1.20 × 10 -4 m, and the wire pitch p is 5.08 × 10 -4 m, the electrostatic chuck 100 of Example 4 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 4, the value of the index Cs was 389.5. When the electrostatic capacitance of the electrostatic chuck 100 of Example 4 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 50.0 pF, and the variation in the electrostatic capacitance was 7.3%.
[0032] [Example 5] The electrostatic chuck 100 of Example 5 has a mesh size of 80 pieces / inch and a ceramic insulating layer thickness D of 7.00×10 -4 m, and the wire diameter a is 6.00 × 10 -5 m, and the wire pitch p is 3.18 × 10 -4m, the electrostatic chuck 100 of Example 5 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 5, the value of the index Cs was 582.3. When the electrostatic capacitance of the electrostatic chuck 100 of Example 5 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 83.9 pF, and the variation in the electrostatic capacitance was 6.0%.
[0033] [Example 6] The electrostatic chuck 100 of Example 6 has a mesh size of 80 pieces / inch and a ceramic insulating layer thickness D of 3.00×10 -4 m, and the wire diameter a is 8.00 × 10 -5 m, and the wire pitch p is 3.18 × 10 -4 m, the electrostatic chuck 100 of Example 6 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 6, the value of the index Cs was 754.5. When the electrostatic capacitance of the electrostatic chuck 100 of Example 6 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 99.8 pF, and the variation in the electrostatic capacitance was 4.8%.
[0034] [Example 7] The electrostatic chuck 100 of Example 7 has a mesh size of 80 pieces / inch and a ceramic insulating layer thickness D of 5.00×10 -4 m, and the wire diameter a is 1.00×10 -4 m, and the wire pitch p is 3.18 × 10 -4 m, the electrostatic chuck 100 of Example 7 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 7, the value of the index Cs was 699.9. When the electrostatic capacitance of the electrostatic chuck 100 of Example 7 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 99.8 pF, and the variation in the electrostatic capacitance was 5.5%.
[0035] [Example 8] The electrostatic chuck 100 of Example 8 has a mesh size of 80 pieces / inch and a ceramic insulating layer thickness D of 1.00×10 -3m, and the wire diameter a is 1.20 × 10 -4 m, and the wire pitch p is 3.18 × 10 -4 m, the electrostatic chuck 100 of Example 8 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 8, the value of the index Cs was 623.2. When the electrostatic capacitance of the electrostatic chuck 100 of Example 8 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 88.8 pF, and the variation in the electrostatic capacitance was 3.6%.
[0036] [Example 9] The electrostatic chuck 100 of Example 9 has a mesh size of 80 wires / inch and a wire pitch p of 3.18×10 -4 m, the electrostatic chuck 100 of Example 9 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 9, the value of the index Cs was 805.1. When the electrostatic capacitance of the electrostatic chuck 100 of Example 9 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 113.3 pF, and the variation in the electrostatic capacitance was 3.7%.
[0037] [Example 10] The electrostatic chuck 100 of Example 10 has a mesh size of 100 pieces / inch and a ceramic insulating layer thickness D of 3.00×10 -4 m, and the wire diameter a is 8.00 × 10 -5 m, and the wire pitch p is 2.54 × 10 -4 m, the electrostatic chuck 100 of Example 10 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 10, the value of the index Cs was 943.1. When the electrostatic capacitance of the electrostatic chuck 100 of Example 10 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 132.5 pF, and the variation in the electrostatic capacitance was 0.3%.
[0038] [Example 11] The electrostatic chuck 100 of Example 11 has a mesh size of 100 pieces / inch and a ceramic insulating layer thickness D of 1.20×10 -3m, and the wire diameter a is 1.00×10 -4 m, and the wire pitch p is 2.54 × 10 -4 m, the electrostatic chuck 100 of Example 11 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 11, the value of the index Cs was 724.0. When the electrostatic capacitance of the electrostatic chuck 100 of Example 11 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 89.1 pF, and the variation in the electrostatic capacitance was 9.9%.
[0039] [Example 12] The electrostatic chuck 100 of Example 12 has a mesh size of 100 pieces / inch and a ceramic insulating layer thickness D of 1.00×10 -3 m, and the wire diameter a is 1.20 × 10 -4 m, and the wire pitch p is 2.54 × 10 -4 m, the electrostatic chuck 100 of Example 12 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 12, the value of the index Cs was 779.0. When the electrostatic capacitance of the electrostatic chuck 100 of Example 12 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 111.0 pF, and the variation in the electrostatic capacitance was 5.2%.
[0040] [Example 13] The electrostatic chuck 100 of Example 13 has a mesh size of 120 pieces / inch and a ceramic insulating layer thickness D of 1.00×10 -3 m, and the wire diameter a is 4.00 × 10 -5 m, and the wire pitch p is 2.12 × 10 -4 m, the electrostatic chuck 100 of Example 13 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 13, the value of the index Cs was 762.7. When the electrostatic capacitance of the electrostatic chuck 100 of Example 13 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 110.1 pF, and the variation in the electrostatic capacitance was 7.7%.
[0041] [Example 14] The electrostatic chuck 100 of Example 14 has a mesh size of 120 pieces / inch and a ceramic insulating layer thickness D of 1.20×10 -3 m, and the wire diameter a is 4.00 × 10 -5 m, and the wire pitch p is 2.12 × 10 -4 m, the electrostatic chuck 100 of Example 14 is similar to the electrostatic chuck 100 of Example 1. In the electrostatic chuck 100 of Example 14, the value of the index Cs was 740.5. When the electrostatic capacitance of the electrostatic chuck 100 of Example 14 was measured by the same method as in Example 1, the average value of the measurements at 53 points was 106.4 pF, and the variation in the electrostatic capacitance was 1.3%.
[0042] [Example 15] In the electrostatic chuck 100 of the fifteenth embodiment, the electrostatic attraction electrode 124 is formed of Mo foil. -5 m, and the pitch p (the center-to-center distance between adjacent electrode portions 124e) is 6.00×10 -4 m, and the thickness D of the ceramic insulation layer is 1.50×10 -4 m. In the electrostatic chuck 100 of Example 15, the value of the index Cs was 399.3. When the electrostatic capacitance of the electrostatic chuck 100 of Example 15 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 53.3 pF, and the variation in the electrostatic capacitance was 6.0%.
[0043] [Example 16] In the electrostatic chuck 100 of the sixteenth embodiment, the electrostatic attraction electrode 124 is formed of Mo foil. -5 m, and the pitch p (the center-to-center distance between adjacent electrode portions 124e) is 5.00×10 -4 m, and the thickness D of the ceramic insulation layer is 3.00×10 -4m. In the electrostatic chuck 100 of Example 16, the value of the index Cs was 404.7. When the electrostatic capacitance of the electrostatic chuck 100 of Example 16 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 54.9 pF, and the variation in the electrostatic capacitance was 9.8%.
[0044] [Example 17] In the electrostatic chuck 100 of the seventeenth embodiment, the electrostatic attraction electrode 124 is formed of Mo foil. -4 m, and the pitch p (the center-to-center distance between adjacent electrode portions 124e) is 6.00×10 -4 m, and the thickness D of the ceramic insulation layer is 5.00×10 -4 m. In the electrostatic chuck 100 of Example 17, the value of the index Cs was 388.0. When the electrostatic capacitance of the electrostatic chuck 100 of Example 17 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 50.0 pF, and the variation in the electrostatic capacitance was 4.1%.
[0045] [Comparative Example 1] The electrostatic attraction electrode 124 of the electrostatic chuck 100 of Comparative Example 1 was formed using a mesh of plain-woven Mo wires. The electrostatic chuck 100 of Comparative Example 1 had a mesh size of 40 wires / inch and a ceramic insulating layer thickness D of 7.00×10 -4 m, and the wire diameter a is 6.00 × 10 -5 m, and the wire pitch p is 6.35 × 10 -4 m. In the electrostatic chuck 100 of Comparative Example 1, the value of the index Cs was 291.2. When the electrostatic capacitance of the electrostatic chuck 100 of Comparative Example 1 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 40.8 pF, and the variation in the electrostatic capacitance was 14.1%.
[0046] [Comparative Example 2] The electrostatic attraction electrode 124 of the electrostatic chuck 100 of Comparative Example 2 was formed using a mesh of plain-woven Mo wires. The electrostatic chuck 100 of Comparative Example 2 had a mesh size of 40 wires / inch and a ceramic insulating layer thickness D of 5.00×10 -4 m, and the wire diameter a is 1.00×10 -5 m, and the wire pitch p is 6.35 × 10 -4 m. In the electrostatic chuck 100 of Comparative Example 2, the value of the index Cs was 350.0. When the electrostatic capacitance of the electrostatic chuck 100 of Comparative Example 2 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 42.2 pF, and the variation in the electrostatic capacitance was 15.8%.
[0047] [Comparative Example 3] The electrostatic attraction electrode 124 of the electrostatic chuck 100 of Comparative Example 3 was formed using a mesh of plain-woven Mo wires. The electrostatic chuck 100 of Comparative Example 3 had a mesh size of 40 wires / inch and a ceramic insulating layer thickness D of 1.00×10 -3 m, and the wire diameter a is 1.20 × 10 -4 m, and the wire pitch p is 6.35 × 10 -4 m. In the electrostatic chuck 100 of Comparative Example 3, the value of the index Cs was 311.6. When the electrostatic capacitance of the electrostatic chuck 100 of Comparative Example 3 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 41.8 pF, and the variation in the electrostatic capacitance was 13.7%.
[0048] [Comparative Example 4] The electrostatic attraction electrode 124 of the electrostatic chuck 100 of Comparative Example 4 was formed using a mesh of plain-woven Mo wires. The electrostatic chuck 100 of Comparative Example 4 had a mesh size of 50 wires / inch and a ceramic insulating layer thickness D of 7.00×10 -4 m, and the wire diameter a is 6.00 × 10 -5 m, and the wire pitch p is 5.08 × 10 -4m. In the electrostatic chuck 100 of Comparative Example 4, the value of the index Cs was 364.0. When the electrostatic capacitance of the electrostatic chuck 100 of Comparative Example 4 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 45.8 pF, and the variation in the electrostatic capacitance was 19.2%.
[0049] [Comparative Example 5] In the electrostatic chuck 100 of Comparative Example 5, the electrostatic attraction electrode 124 is formed of Mo foil. -4 m, and the pitch p (the center-to-center distance between adjacent electrode portions 124e) is 1.00×10 -3 m, and the thickness D of the ceramic insulation layer is 1.00×10 -3 m. In the electrostatic chuck 100 of Comparative Example 5, the value of the index Cs was 197.9. When the electrostatic capacitance of the electrostatic chuck 100 of Comparative Example 5 was measured in the same manner as in Example 1, the average value of the measurements at 53 points was 24.7 pF, and the variation in the electrostatic capacitance was 14.0%.
[0050] <Effects of the embodiment> In the above embodiment, the electrostatic chuck 100 includes a ceramic base 110 and a metal electrostatic attraction electrode 124 embedded in the ceramic base 110. The electrostatic attraction electrode 124 is formed of a mesh, foil, or plate material made of woven metal wires. When the electrostatic attraction electrode 124 is formed of a mesh made of woven metal wires, the wire diameter (diameter) is a (m), the wire pitch is p (m), and the insulating layer thickness is D (m). The wire pitch p is the center-to-center distance between adjacent wires, and the insulating layer thickness D is the vertical distance between the upper surface 111 of the ceramic base 110 and the electrostatic attraction electrode 124. When the electrostatic attraction electrode 124 is formed of a foil or plate material, openings 124h are formed so that electrode portions 124e having a width a (m) are arranged at a pitch p (m). The electrode parts 124e are arranged at a pitch p(m), which means that the center-to-center distance between the electrode parts 124e adjacent to each other in one direction is p(m). Comparing Examples 1 to 17 with Comparative Examples 1 to 5, it was found that by setting the index Cs=[1 / ln{10(2D-a) / a}] / p to 375 or more, it is possible to suppress the variation in the capacitance to within 10% while securing a sufficient capacitance (50 pF or more) for the electrostatic chuck 100. In other words, it was found that by selecting the thickness D of the ceramic insulating layer, the pitch p, and the wire diameter a (width a of the electrode part 124e) so that the index Cs is 375 or more, which is the lower limit, it is possible to suppress the variation in the capacitance to within 10% while securing a sufficient capacitance (50 pF or more) for the electrostatic chuck 100, even if the electrostatic attraction electrode 124 has a certain porosity.
[0051] As in the above-mentioned Examples 1 to 14, the electrostatic attraction electrode 124 may be an electrode of a metal mesh in which metal wires such as Mo are woven. Alternatively, as in the above-mentioned Examples 15 to 17, the electrostatic attraction electrode 124 may be an electrode of a metal foil or a metal plate in which the openings 124h of width b (m) (b=pa) are formed so that the electrode parts 124e of width a (m) are arranged in one direction at a pitch p (m). In either case, the variation in the electrostatic capacitance can be suppressed to within 10% while securing a sufficient electrostatic capacitance (50 pF or more) for the electrostatic chuck 100. The shape of the opening of the openings 124h does not necessarily have to be a rectangle, and may be a polygon other than a rectangle. For example, as shown in FIG. 10, the shape of the opening of the openings 124h may be a hexagon. Even in this case, as shown in FIG. 10, it is possible to define the width a of the electrode portion 124e, the width b of the opening portion 124h, and the pitch p, which is the center-to-center distance between two adjacent electrode portions 124e in one direction (the horizontal direction in FIG. 10).
[0052] As in the above Examples 1 to 17, the size of the pitch p is 2.00 × 10 -4 m or more 7.00×10 -4m or less. Even when the pitch p is relatively large and the area of the opening portion 124h of the electrostatic attraction electrode 124 is relatively large, a sufficient electrostatic capacitance (50 pF or more) can be ensured by selecting the thickness D of the ceramic insulating layer and the wire diameter a (width a of the electrode portion 124e) so that the value of the index Cs is 375 or more. In addition, by increasing the area of the opening portion 124h, the contact area between the electrode portion 124e of the electrostatic attraction electrode 124 and the ceramic insulating layer constituting the ceramic base material 110 can be reduced. This makes it possible to suppress the occurrence of peeling at the interface between the electrode portion 124e and the ceramic insulating layer, and to reduce the residual stress at the interface between the electrode portion 124e and the ceramic insulating layer. This suppresses peeling and distortion at the interface between the electrode portion 124e and the ceramic insulating layer, making it easy to uniformly process the ceramic insulating layer, and suppressing local variations in the thickness of the ceramic insulating layer. As a result, it is possible to suppress the occurrence of local abnormalities in electrostatic capacitance, and suppress variations in electrostatic capacitance over the entire surface of the electrostatic chuck.
[0053] As in the above Examples 1 to 3, 6, 7, 9, 10, and 15 to 17, the thickness D of the ceramic insulating layer was set to 1.00 × 10 -4 m or more 5.00×10 -4 m or less. Even when the thickness D of the ceramic insulating layer is relatively thin, by selecting the pitch p and the wire diameter a (width a of the electrode portion 124e) so that the value of the index Cs is 375 or more, it is possible to ensure a sufficient capacitance (50 pF or more), suppress the occurrence of peeling at the interface between the electrode portion 124e and the ceramic insulating layer, and reduce the residual stress at the interface between the electrode portion 124e and the ceramic insulating layer. This suppresses peeling and distortion at the interface between the electrode portion 124e and the ceramic insulating layer, making it easy to uniformly process the ceramic insulating layer and suppressing local variations in the thickness of the ceramic insulating layer. As a result, it is possible to suppress the occurrence of local capacitance abnormalities and suppress variations in capacitance over the entire surface of the electrostatic chuck.
[0054] <Modification form> The above-described embodiment is merely an example and may be modified as appropriate. For example, the shape, size, and thickness of the electrostatic attraction electrode 124 are not limited to those in the above-described embodiment and may be modified as appropriate.
[0055] Furthermore, the shape, thickness, etc. of the ceramic base 110 may be appropriately changed. Furthermore, the dimensions, such as the height and width, and the shape of the annular convex portion and the multiple convex portions may be appropriately changed.
[0056] The electrostatic chuck 100 of the present embodiment may include a heater electrode (not shown) embedded in the ceramic base 110. This allows the electrostatic chuck 100 to be provided with a heating function.
[0057] Although the present invention has been described above using the embodiment and its modified form, the technical scope of the present invention is not limited to the above description. It is obvious to those skilled in the art that various modifications or improvements can be made to the above embodiment. It is also clear from the claims that such modifications or improvements can be included in the technical scope of the present invention.
[0058] The order of execution of each process in the manufacturing method shown in the specification and drawings is not particularly specified, and may be any order unless the output of a previous process is used in a subsequent process. For convenience, even if the description uses "first," "next," etc., it does not mean that the process must be performed in that order. [Explanation of symbols]
[0059] 100 Electrostatic Chuck 110 Ceramic substrate 124 Electrostatic Adsorption Electrode 124e Electrode part 124h opening part
Claims
1. A ceramic substrate having an upper surface and a lower surface facing the upper surface in a vertical direction; A metal electrode embedded in the ceramic substrate, In the electrode, electrode portions having a width a (m) and openings having a width b (m) are alternately arranged in a first direction perpendicular to the up-down direction, When the distance in the vertical direction from the upper surface of the ceramic base to the electrode is D (m) and the sum of the width a (m) and the width b (m) is p (m), the index Cs is expressed as: Cs=[1 / ln{10(2D-a) / a}] / p≧375 The electrostatic chuck is characterized by:
2. 2. The electrostatic chuck according to claim 1, wherein the electrode is a mesh electrode formed by plain weaving wires having a diameter a (m).
3. 2. The electrostatic chuck according to claim 1, wherein the electrode is a metal foil or a metal plate in which the openings having a width b (m) are formed such that the electrode portions having a width a (m) are arranged at intervals of b (m) in the first direction.
4. 2.00×10 -4 (m)≦p≦7.00×10 -4 (m) The electrostatic chuck according to any one of claims 1 to 3, wherein
5. 1.00×10 -4 (m)≦D≦5.00×10 -4 (m) The electrostatic chuck according to any one of claims 1 to 3, wherein
Citation Information
Patent Citations
Electrostatic chuck or electrode built-in susceptor
JP2017212375A